Real Eigenvalues of Viscoelastic Oscillators Involving Several Damping Models - Kostić, Aleksandra; Voss, Heinrich (Sarajevo Journal of Mathematics, 2018)
This paper presents the dynamic analysis of a system involving various damping models. The free motion equation can be transformed to a system containing only exponentially decaying damping. Its real eigenvalues can be characterized as maxmin values of a Rayleigh functional and can be determined by the quadratically convergent saveguarded iteration. A numerical example demonstrates the efficiency of the approach.